Pengaruh Gaya Kepemimpinan dan Stres Kerja terhadap Motivasi Kerja Karyawan PT Telkom Indonesia Witel Bekasi - Khalifah Fathan Maulana; Zahra Zahra; Athiy Dina Rosihana (Jurnal Riset dan Inovasi Manajemen, 2025)
PT Telkom Indonesia is a state-owned telecommunications and information technology company in Indonesia that provides various digital and telecommunication services. The data collection technique used is non-probability sampling with a saturated sampling technique. This study uses a quantitative approach with data collected through research instruments. The data analysis techniques used include instrument testing, descriptive analysis, classical assumption tests, multiple linear regression analysis, the coefficient of determination test, and hypothesis testing using SPSS 26. The results of the study show that the t-count value for the Leadership Style variable is less than the t-table value (0.922 < 2.042) and the significance value in the t-test is 0.364 > 0.05. This indicates that Leadership Style (X1) does not have a significant effect on Work Motivation (Y) of employees at PT Telkom Indonesia Witel Bekasi. Meanwhile, the t-count value for the Work Stress variable is also less than the t-table value (-0.480 < 2.042) and the significance value is 0.635 > 0.05. Thus, it can be concluded that Work Stress (X2) does not have a negative or significant effect on Work Motivation (Y) of employees at PT Telkom Indonesia Witel Bekasi. Simultaneously, both Leadership Style (X1) and Work Stress (X2) do not have a significant effect on Work Motivation (Y). This is shown by the F-test result, where the F-count value (0.523) is lower than the F-table value (3.316), and the significance value of 0.598 is greater than 0.05.